PENGARUH KOMUNIKASI DAN DUKUNGAN ORGANISASIONAL TERHADAP EMPLOYEE ENGAGEMENT PADA FRONTLINER SMALL AREA DI PT. ISS INDONESIA CABANG BATAM - Efendy, Risman; Nasution, Ade Parlaungan (University of Riau Kepulauan, 2015)
The purpose of this study was to determine the effect of communication and organizational support on employee engagement, either separately (partial) or jointly (simultaneously).Â In this study, the authors used a sample of 78 employees were taken at random from the total population of 110 employees. While the types of data used are primary data and secondary data. Sources of primary data obtained from questionnaires with employees who are competent at. ISS Indonesia Batam Branch. While the sources of secondary data obtained from the document PT. ISS IndonesiaBatam Branch and obtained from related literature and can support as well as useful for this research. Data was collected by distributing questionnaires.Â Data were analyzed by descriptive statistics, which are used to describe the objects that give an overview of the study through the data obtained from a population sample in the field associated with the relevant theories and techniques of quantitative analysis of the data that has been given a score according to the scale of measurement used the Likert scale and to the results of the test using SPSS (Statistical Product and Service Solutions) version 20.Â From the research, the authors conclude that the partial Communications (X1) and a significant positive effect on Employee Engagement (Y), with test results of 0.295 or 29.5%, while the Organizational Support (X2) is also positive and significant effect on Employee Engagement ( Y), it is seen from the test results of 0.405 or 40.5%. But simultaneously Communications and Organizational Support positive and significant effect (strong) on Employee Engagement at PT. ISS Indonesia Batam Branch to sled for 0624 or 62.4%, as for the rest of 0376 or 37.6% influenced by variables or other factors.